Scale effects of the rheological properties of electrorheological suspensions. (September 2015) - Freyer, Holger; Breitfeld, Andreas; Ulrich, Stephan; Schneider, Steffen; Bruns, Rainer; Wulfsberg, Jens
The knowledge about the rheological behavior of electrorheological suspensions in all prevalent conditions is essential for the design process of applications. Of particular importance is the dependence of fluid viscosity on the electric field strength, the temperature, and the shear rate. Previous research has pointed out the difficulties in determining the relevant rheological parameters independent from the geometry and flow conditions. For example, experimental results obtained using a capillary rheometer are different from the results gained in flow channel experiments. Even the results from one flow channel could not easily be used to predict the performance of a channel with, for example, a different distance between the electrodes. Some possible effects such as wall slip, interactions of the particles with the surface of the electrodes, or scale effects based on the particle size distribution in relation to the dimension of the flow channel may complicate the determination of the rheological parameters. To investigate these effects, a flow channel test rig that allows systematic changes to the flow conditions was developed. The distance of the electrodes can continuously be changed from 0.02 to 1 mm with an apparent shear rate from 100 to 10, 000 s −1 . The electrodes can easily be replaced to determine the influence of surface structure. This article will first discuss the design of the flow channel followed by the experimental results obtained under different test conditions. The aim of this research is to gain insight into the scale effects of electrorheological suspensions in order to develop microfluidic applications.